Penanganan Perkara Tindak Pidana Manipulasi Data dan Pengancaman Melalui Media Sosial pada Direktorat Reserse Kriminal Khusus Polda Nusa Tenggara Timur - Angela Dima; Rudepel Petrus Leo; Bhisa Vitus Wilhelmus (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid development of information technology has contributed to the increasing occurrence of cybercrime, particularly data manipulation and threats through social media. This study aims to analyze the handling of criminal cases involving data manipulation and threats through social media by the Cyber Crime Directorate of the Special Criminal Investigation Directorate of the East Nusa Tenggara Regional Police and to identify the factors influencing the effectiveness of law enforcement. This research employed an empirical legal method with a case approach. Primary data were collected through interviews with investigators of the Cyber Crime Subdirectorate of the East Nusa Tenggara Regional Police, while secondary data were obtained from legislation, legal literature, court decisions, and related scientific publications. The findings indicate that all reported cases during the 2023–2026 period were successfully processed through investigation and transferred to the public prosecutor in accordance with Law Number 1 of 2024 concerning Electronic Information and Transactions. Nevertheless, law enforcement remains constrained by limited digital forensic facilities, the rapid deletion or alteration of electronic evidence, the increasing misuse of Artificial Intelligence (AI), and low public digital literacy. Strengthening investigators' competencies, improving digital forensic infrastructure, enhancing interagency cooperation, and expanding digital literacy programs are essential to improve the effectiveness of cybercrime law enforcement.